Exploring The Association Between Spirituality And Depression Among Adults In Ahmedabad City - Nitin Thakor; Pravender (Moroccan Journal of Quantitative and Qualitative Research)
Depressive symptoms and spiritual practices are prevalent worldwide, yet their interconnectedness has received limited attention from mental health professionals. This quantitative study delves into the association between spiritual engagement and depressive symptoms or disorders. Religious beliefs and rituals may offer coping mechanisms for individuals facing stressful life circumstances, providing them with a sense of purpose and hope, and fostering a supportive community for those experiencing unhappiness. The study aims to ascertain whether spiritual factors act as a protective resource or a potential burden in adults.